2023
DOI: 10.3390/agriculture13061187
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Available Straw Nutrient Resources and Substitution of Chemical Fertilizers with Straw Returned Directly to the Field in China

Abstract: Returning straw to the field is the most significant straw utilization technique for China’s green development. It can provide nutrients for crop growth and improve soil organic matter content. However, there are no standard parameters for measuring the nutrient content of straw directly returned to the field. In addition, the nutrient content of straw in the field is disregarded and the least researched. Therefore, to address these issues, the current research examines the main nutrient composition of straw r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Previous reports have shown that straw return improved the soil N content and N uptake and reduces the soil N leaching (Huang et al, 2021). Besides, the decomposition of straw released C, N, P, and K into the soil, improving the soil nutrient status (Tables 2, S5, S6), which is in line with the report by Cui et al (2020a) and Shao et al (2023). According to the SEM analysis (Fig.…”
Section: Effect Of Straw Return On Nuesupporting
confidence: 90%
See 2 more Smart Citations
“…Previous reports have shown that straw return improved the soil N content and N uptake and reduces the soil N leaching (Huang et al, 2021). Besides, the decomposition of straw released C, N, P, and K into the soil, improving the soil nutrient status (Tables 2, S5, S6), which is in line with the report by Cui et al (2020a) and Shao et al (2023). According to the SEM analysis (Fig.…”
Section: Effect Of Straw Return On Nuesupporting
confidence: 90%
“…Possible reasons for this are that the positive impact of straw return on yield can be influenced by environmental conditions and management practices, which are closely related to the straw decomposition status. One of the major reasons for improvement in crop yield under straw return is the promotion of nutrient availability in the soil during straw degradation (Turmel et al, 2015;Shao et al, 2023). Our study observed a significant increase in soil Nmin, available P, and exchangeable K under straw return treatment (Table 2), which proved that the basic productivity of soil was enhanced after a 3-year straw return.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The straw mulch leads to an improvement in soil chemical properties through increasing the concentration of available forms of macronutrients (N, P, K) and organic carbon in the top layers of soil [29][30][31]. According to Shao et al [32], nutrients from straw mineralization may be an effective source of nitrogen, phosphorus and potassium, replacing 10% N, 9% P 2 O 5 and 58% K 2 O from fertilizer application.…”
Section: Introductionmentioning
confidence: 99%
“…The negative aspects of mulching the soil with straw include the possibility to increase pests and diseases infestation in main crops [25,33,34]. Shao et al [32] stated that incorrect direct straw-returning practices may have negative effects for crop health and the number of pests and may also reduce the crop germination rate. However, the results of research on this issue are not clear.…”
Section: Introductionmentioning
confidence: 99%